Relevance and clinical implications of tumor cell mobilization in the autologous transplant setting - DiPersio, John F.; Ho, Anthony Dick; Hanrahan, Jessie; Hsu, Frank J.; Fruehauf, Stefan (Biology of blood and marrow transplantation, 2011)
Autologous transplantation of peripheral blood (PB) hematopoietic stem cells (HSCs) is a widely used strategy for reconstitution of blood cells following high-dose chemotherapy for hematologic malignancies such as multiple myeloma (MM), non-Hodgkin lymphoma (NHL), and acute myeloid leukemia (AML), among others. Stem cells for transplantation are usually obtained from PB after treatment with chemotherapy with or without cytokine, usually granulocyte-colony stimulating factor (G-CSF), or after treatment with cytokine alone. The use of autologous peripheral blood stem cells (PBSCs) for transplantation is associated with the risk of contamination of the graft with tumor cells; whether this impacts response rates, progression-free survival (PFS), and overall survival (OS) is still debatable. This review summarizes the controversy surrounding tumor cell mobilization (TCM), the complexity of detection of minimal residual diseases, the available diagnostic tools, differences in TCM with available mobilization regimens, and the potential effect of TCM on clinical outcome. Collectively, these data suggest that new treatment paradigms to manage hematologic malignancies, such as MM, NHL, and AML, are needed and should focus on increasing the chemosensitivity of the tumor and eliminating residual disease.